A smart building material for low/zero carbon applications: heat insulation solar glass—characteristic results from laboratory andin situtests - Cuce, Erdem; Riffat, Saffa (Oxford University Press, 2017)
Heat insulation solar glass (HISG) is a recently developed smart building material to minimize energy consumption of building sector. HISG might be presumed to be a conventional photovoltaic glazing product; however, it is completely unique by having some characteristic features such as superior thermal insulation, which is competitive with triple-glazed windows using argon as inert gas, acoustic and thermal comfort, self-cleaning ability owing to TiO2 nano-coating on module surface and extraordinary energy saving potential in both summer and winter. In our previous works, comprehensive experimental and numerical works have been carried out for power generation and thermal insulation performance of HISG under various climatic conditions. Within the scope of this research, optical- and lighting-related performance parameters of this smart building material are evaluated through extensive laboratory and in situ tests. Shading coefficient, visible light intensity, and UV and IR penetration are investigated via the tests conducted in real operating conditions. It is achieved from the results that the shading coefficient of HISG is only 0.136, which yields almost 80% reduction in solar heat gain compared with ordinary glazing. It is also observed from the in situ tests that HISG has a %100 UV and 99% IR blocking rate, which is of vital importance in terms of human health and thermal comfort conditions. Glaring effects are totally resolved via HISG, which is still a challenge for the buildings with conventional glazing products, especially in summer.